Assessing the potency of vitamin D augmentation on saccharometric indices in type 2 diabetes: a meta-analysis - Gong, Su; Chen, Li (Frontiers in Nutrition, 2026)
BackgroundThis meta-analytical investigation sought to elucidate the therapeutic efficacy and tolerability of vitamin D supplementation in modulating glycemic indices among individuals diagnosed with type 2 diabetes (T2D).MethodsSystematic searches were performed across PubMed, Embase, Web of Science, Cochrane Library, and Chinese databases (CNKI and Wanfang) to identify relevant randomized controlled trials (RCTs). Studies were deemed eligible if they enrolled adult T2D populations, administered vitamin D interventions, and reported outcomes including glycated hemoglobin (HbA1c), homeostasis model assessment of insulin resistance (HOMA-IR), or serum 25-hydroxyvitamin D [25(OH)D] concentrations.ResultsTen RCTs, encompassing a total of 3,460 participants, met inclusion criteria. Intervention durations varied between 3 and 12 months, and dosing regimens ranged from 500 IU and 60,000 IU. Pooled analysis revealed a significant increase in serum 25(OH)D levels following supplementation (SMD: 4.01; 95% CI: 2.43 to 5.59; p < 0.001; I2 = 99.3%). In contrast, no statistically significant improvements were observed in HbA1c (SMD: 0.08; 95% CI: −0.25 to 0.37; p < 0.001; I2 = 86.5%) or HOMA-IR (SMD: 5.95; 95% CI: −2.87 to 14.77; p < 0.001; I2 = 100.0%). Adverse event profiles were similar between the vitamin D and control groups (RR: 1.19; 95% CI: 0.79 to 1.80; p = 0.183; I2 = 43.5%).ConclusionVitamin D supplementation yield a consistent rise in serum 25(OH)D concentrations but exerts no discernible effect on glycemic regulation or insulin sensitivity in T2D populations. The favorable safety profile supports its tolerability. Considerable heterogeneity in metabolic outcomes underscores the need for future investigations stratified by baseline vitamin D status, enhancement regimen, and study duration.